A SECOND ALLOGENEIC HEMATOPOIETIC CELL TRANSPLANT (HCT2) MAY CURE MORE THAN 40% PEDIATRIC PATIENTS WITH HEMATOLOGICAL MALIGNANCIES - MF Cardoso; G Zamperlini; CNM Breviglieri; R Gouveia; VC Ginani; JF Marques; LL Quintino; LDS Domingues; MGAD Matos; A Seber (Hematology, Transfusion and Cell Therapy, 2023)
Introduction: Relapse of a malignant hematological disease after allogeneic HCT is associated with poor survival and may not be treated with a curative intent. However, a second HCT (HCT2) may achieve durable remission. Objective: To determine the outcomes of pediatric patients who received a HCT2 for relapsed malignant hematological diseases. Casuistic and method: Review of the medical records of pediatric patients who underwent a HCT2 for relapsed malignant hematological diseases in two institutions from 2013 to 2023. OS was estimated using Kaplan-Meier survival analysis. The conventional HCT Comorbidity index (HCT-CI) was calculated for all patients (http://www.hctci.org/Home/Calculator) categorized in < or ≥ 2. Results: Nineteen patients with a median age of 10 years (range, 2–17) underwent HCT2 for B-ALL (n = 8), T-ALL (n = 2), AML (n = 5), CML-BC (n = 2), MDS (n = 1) and JMML (n = 1). Donor types were unrelated (n = 4), haploidentical (n = 11), and unrelated cord-blood (n = 4). Donors were different at HCT2 in all patients and all haploidentical HCT2 used the other haplotype. All nineteen patients received myeloablative conditioning, and 52% (n = 10) were in remission at HCT2. The median remission duration after HCT1 was 12 months (range, 2–22) and the median time between transplants was 16 months (range, 5–30). The median follow-up of surviving patients after HCT2 was 33 months (range, 9–117), with 47% alive at time of analysis. The most common cause of death was disease recurrence (n = 6, 31%). At time of analysis, OS, PFS, relapse, and Transplant-Related Mortality (TRM) were 47% , 42%, 45%, and 21%, respectively. OS was 37% (3/8) for B-ALL. All T-cell ALL, CML-BC, MDS and JMML patients are alive, but all 5 patients with AML have died. None of the latter have used post-HCT maintenance to prevent relapse. Pre-HCT2 remission status did not appear to influence OS and PFS, since of 11 patients in remission, 5 remain alive and disease-free. Of the 8 patients transplanted with active disease, 6 remain in remission. Ten patients had HCT-CI < 2 pre HCT2, and 3 of 10 have died. However, 7 out of 9 patients with HCT-CI score ≥ 2 died (HR = 4.8, p = 0.007). Conclusion: A second HCT can be feasible for patients with relapsed malignant hematological diseases. Overall survival is higher than 40%, suggesting that this approach may cure a proportion of the patients, particularly those with HCT-CI < 2 pre HCT2.